Nosologie Des Enfants Dits Atypiques Dans La Societe Baoule (Cote D’ivoire) - Patrice, KACOU Fato; Daouda, DOUKOURE; Amédée-Pierre, ATSE Achi (European Scientific Journal, ESJ, 2016)
The study analyses the social mechanisms that govern the acceptance of children in Baoule society. It is clear to open a window on the social frames of reference from which, on the one hand, we refer to the so-called atypical children and on the other hand to classify them.. To do this, using qualitative approches, we collected data from a sexagenarian Baoulé tradi-prationer based in Bouaké, selected according to our target. The investigations led to the result that the social representations of pregnancy and child in the Baoulé society call for the observation of taboos during pregnancy and structure the typology of so-called mis fortune children. They also determine the social solutions to the cases of evil called children. That requires the urgent adoption of an interdisciplinary approch that puts together at least human and health sciences in the treatement of problems linked to infant mortality and beloyond, changes social perceptions in order to keep alive the so-called atypical children, codemned to death or socially marginalized.